Stochastic Finance : a Numeraire Approach. - Vecer, Jan (Chapman & Hall/CRC financial mathematics series., 2011)
... a nice book for researchers and practitioners. ... this book can be regarded as a wonderful application of stochastic analysis, as it includes not only detailed theoretical proofs but also practical illustrative examples. With the systematic and feasible numeraire techniques, the book can serve as an everyday reference book for practitioners, but also as a powerful tool to deal with pricing and hedging for complicated financial assets. Most importantly, the representation of prices as a pairwise relationship of two assets is the most novel characteristic of this book, which could lead to deepe.